Comparative Study on the Physicochemical and Volatile Compounds of Dalbergia odorifera T. Chen Honey From Guizhou, China, and Honey From Different Floral Sources - Haoxiang Xu; Qingfeng Wang; Ting Li; Bo Yu; Yuanfeng Zhao; Ran Jiang; Jing Rui Zhou; Juan Li; Lu Lei (Journal of Food Quality)
This study compared the physicochemical properties and characteristic volatile compounds of honey samples from Guizhou, China (such as Dalbergia odorifera T, Rhus chinensis Mill, blueberry, and loquat honey), and Manuka honey. The moisture content, 5-HMF, antioxidant capacity, sugars, amino acids, minerals, and volatile compounds were measured. The results indicated that all honey samples met the standards of the Chinese honey industry. Using GC × GC-TOF MS technology, 927 volatile substances were detected in Dalbergia odorifera T. Chen honey, 930 in Manuka honey, 764 in Rhus chinensis Mill honey, 768 in blueberry honey, and 617 in loquat honey. The study described the volatile compounds and sensory characteristics of each honey. The main volatile compounds identified in all samples were hydrocarbons, aldehydes, esters, ketones, and alcohols, with predominant sensory flavors of sweet, green, and floral notes.